Maternal and fetal outcome in gestational diabetes mellitus - Dudhwadkar, Ameya R.; Fonseca, Michelle N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Indian women have high prevalence of diabetes and their relative risk of developing gestational diabetes mellitus (GDM) is 11.3 times compared to white women. As such GDM has implications beyond the index pregnancy, identifying two generations (mother and her offspring) at risk of future diabetes. Limited studies in India have compared the outcome and control of GDM. Methods: Patients attending the antenatal OPD or medicine OPD or were admitted in the medicine or obstetric wards were screened for gestational diabetes according to the ADA criteria. Maternal and fetal outcome was studied. Results: The incidence of GDM in the population studied was 4.2%. Pre-eclampsia complicating pregnancy was noted in 26% patients. 46% patients delivered vaginally. 2% deliveries were vacuum assisted. In this study 52% patients underwent LSCS. 40% babies were macrosomic at birth. 8% had congenital anomalies while 2% patients had fresh still birth. Maternal diabetes on follow up was seen in 16.2% patients. Conclusions: Gestational diabetes complicating pregnancy has adverse maternal and fetal outcome. Better identification and treatment of mothers and fetuses at risk may have far-reaching implications for maternal and child health. In conclusion, a short term intensive care gives a long term pay off in the primary prevention of obesity, impaired glucose tolerance and diabetes in the offspring, as preventive medicine starts before birth.